8x-3(x-5)=3x-1

Simple and best practice solution for 8x-3(x-5)=3x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-3(x-5)=3x-1 equation:


Simplifying
8x + -3(x + -5) = 3x + -1

Reorder the terms:
8x + -3(-5 + x) = 3x + -1
8x + (-5 * -3 + x * -3) = 3x + -1
8x + (15 + -3x) = 3x + -1

Reorder the terms:
15 + 8x + -3x = 3x + -1

Combine like terms: 8x + -3x = 5x
15 + 5x = 3x + -1

Reorder the terms:
15 + 5x = -1 + 3x

Solving
15 + 5x = -1 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
15 + 5x + -3x = -1 + 3x + -3x

Combine like terms: 5x + -3x = 2x
15 + 2x = -1 + 3x + -3x

Combine like terms: 3x + -3x = 0
15 + 2x = -1 + 0
15 + 2x = -1

Add '-15' to each side of the equation.
15 + -15 + 2x = -1 + -15

Combine like terms: 15 + -15 = 0
0 + 2x = -1 + -15
2x = -1 + -15

Combine like terms: -1 + -15 = -16
2x = -16

Divide each side by '2'.
x = -8

Simplifying
x = -8

See similar equations:

| 4X^2+380=78X | | 6x-8w+4x+8y+3y+4w= | | (x-5)X(2x+9)=0 | | 5(2x+4)=3(5x+3)+6 | | 4/7-19/28 | | 2x^4(x^3)=0 | | e^1-8x=9 | | 2m*3n=36 | | 6/16=4/c | | 14a+19b+4c+2c-2b-4a= | | Y/6-y=5 | | 2x(x^3)=0 | | u/4-2=-18 | | 2m*3m=36 | | 3(2m+1)=27 | | cos48=x/11 | | -28=2+5v | | xy=-2qx-x^3+2r | | 2(x^3)=0 | | -4=8+u | | 1/4x^2-29/16x-3/2=0 | | 14x-(4x+12)-11x-(3-4x)=0 | | 17=8+3v | | 22y-y^2=72 | | 2x+2y+2+4= | | 5y+17=112 | | 3(x-3)+5=3x-4 | | 15x^4+6x^3-113=0 | | 4x-100=-50 | | y=12x^2-11x-15 | | -6x-1=-11-7x | | (x-i)*(x-i)+(x+i)*(x+i)=0 |

Equations solver categories